EDUCATIONAL AND METHODOLOGICAL OPPORTUNITIES FOR THE FORMATION OF PROFESSIONAL SKILLS IN VOCATIONAL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the educational and methodological opportunities for the formation of professional skills in the preparation of mid-level specialists in the vocational education system, taking into account the requirements of the international labor market.